To what extent does corporate liquidity affect M&A decisions, method of payment and performance? Evidence from China - Yang, Junhong; Guariglia, Alessandra; Guo, Jie (Michael) (Journal of Corporate Finance, 2019)
Using a panel of Chinese listed firms over the period 1998–2015, we examine the extent to which liquidity impacts firms' acquisition decisions, method of payment choice, and performance following mergers. We observe that cash-rich firms are more likely to attempt acquisitions, especially if they are subject to tunneling. Next, we find that bidders with higher growth opportunities are less likely to use cash payments in acquisitions. This effect is stronger for financially constrained bidders, who face greater opportunity costs of holding cash. Our last set of results highlights the under-performance of cash acquisitions in both the short and long term.